Formal Specification Approach for Designing Multiple Types of Spatial Databases Integration Model - Julaily Aida, Jusoh (2012)
Traditionally, most developer prefers not to use formal specification (FS) approach in designing an application system. In recent years, these approach have been seen as rivals, a new consensus has developed in which software developers are agreed it as complementary. Theoretically this approach can reduce the overall development time. FS can be use to provide an unambiguous and precise supplement to natural language descriptions. Focus to this point, it can be rigorously validated and verified leading to the early detection of specification errors or debugs during software development process. Correcting errors at the early development stage is cheaper than modifying a delivered system. FS could be verified and validated in order to explore the consequences of this specification and potentially find mistakes. After it was done, we have greater confidence that the testing of such system against the actual user requirement specification. This paper discusses the FS of Spatial Information Databases Integration Model as a case study.